Pengaruh Persepsi Harga dan Kualitas Layanan Terhadap kepuasan Pengguna Aplikasi Maxim Di Kota Depok - Putri Anggraeni, Anggun; Wartiningsih, Endah; Sofa, Nidia (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
This purposes of this research to establish the impact of perceived price and service quality on user satisfaction of the Maxim application in Depok City. Method uses in this research is the SmartPLS version 4 program with a sample of 100 Maxim users. The output of this study suggest that the price perception variable exerts a positive and significant impact on user satisfaction, as indicated by a p-value 0.001, which is less than 0.05, and a t-statistic of 3.259, which exceeds the critical value of 1.96, this hypothesis is therefore accepted with regression test coefficient value of 0.324 (32%). This shows that the price perception variable makes a strong enough contribution in influencing the level of application user satisfaction. The service quality variable on user satisfaction has a positive and significant impact given that the p-value is 0.000, which is less than 0.05, and the t-statistic is 6.287, exceeding the critical value of 1.96, this hypothesis is consequently accepted with regression test coefficient value show 0.590 (59%). That value indicates the service quality is the main factor affecting user satisfaction.